The Relationship Between Emotional and Other Factors in Information Diffusion - Shuhei Ippa; Takao Okubo; Masaki Hashimoto (IEEE Access)
With the recent proliferation of social media, the spread of disinformation and misinformation has become a global risk. This study analyzes and characterizes the relationship between human emotions and other elements (social bots and echo chambers), which are major factors in the spread of information, including disinformation and misinformation. Specifically, we obtain from X (formerly Twitter) the case that was fact-checked as disinformation in Japan and analyze the relationship between each factor in a time sequence using existing tools and methods. After confirming the similar results to previous studies that emotional posts were more likely to be spread, our analysis showed the possibility that social bots were highly influential in amplifying negative sentiment in the early stages of spread. Regarding emotions and echo chambers, we observed that the increase in negative emotions and the formation of echo chambers followed a similar time sequence. In addition, we confirmed that the amplification of negative emotions precedes the formation of echo chambers. The results of this analysis suggested the importance of detecting social bot activity in the early stages of information diffusion and controlling the amplification of negative emotions.